1990
DOI: 10.1038/eye.1990.95
|View full text |Cite
|
Sign up to set email alerts
|

The success of penetrating keratoplasty for keratoconus

Abstract: We report the results, over a 20 year period up to 1989, of 201 penetrating keratoplasties in 198 eyes of 158 patients. The five year graft survival was 97%. A corrected visual acuity of 6/12 or better was attained by 91%. The mean spherical equivalent refraction on removal of sutures was -2.68 Ds and the mean cylindrical correction was -5.56 Ds. The cumulative time to dispensing final refractive correction was 38 months for 90% of patients. Rejection episodes occurred in 20% of grafts and were associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
16

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 29 publications
4
63
0
16
Order By: Relevance
“…In a retrospective study that analyzed more than 2,000 patients with PK, the incidence of UZS was higher in patients with macular dystrophy than in patients with keratoconus (7) . We believe that patients with ke ratoconus are not at increased risk of UZS, as stated in previous studies (26) . Increased IOP during and immediately after presentation of UZS has been verified in the majority of reported cases; however, the maintenance of ocular hypertension was not clearly demonstrated in these cases (34) .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In a retrospective study that analyzed more than 2,000 patients with PK, the incidence of UZS was higher in patients with macular dystrophy than in patients with keratoconus (7) . We believe that patients with ke ratoconus are not at increased risk of UZS, as stated in previous studies (26) . Increased IOP during and immediately after presentation of UZS has been verified in the majority of reported cases; however, the maintenance of ocular hypertension was not clearly demonstrated in these cases (34) .…”
Section: Discussionsupporting
confidence: 54%
“…Early reports indicated the use of atropine in PK as associated with such complications (1) . Keratoconus was also suggested to be involved in the pathogenesis of UZS as a result of decreased corneal rigidity and enhanced response to mydriatics (3,26) . Intraocular pressure (IOP) elevation, with or without pupillary block, has been implicated as the trigger mechanism of UZS (4,27) .…”
Section: Introductionmentioning
confidence: 99%
“…Different studies on PKP have reported that the 1-year survival rate of donor cornea is up to 90 %, at 5 years it is 88 %, at 10 years it is 80 % and in the 2007 Australian graft report it is 60 % [10][11][12]. Graft clarity rate can reach the extent of 97 % after 4 years in the low-risk group [13]. In transplanted corneas, endothelium can keep its function in some cases even for 30 years [14][15][16][17], with an initial cell density above 2,500 cells/mm 2 ( Table 2).…”
Section: Resultsmentioning
confidence: 93%
“…[7][8][9][10][11][12][13][14] However, this problem has not been adequately highlighted in the UK. 15 In this paper, we report the incidence and outcome of traumatic graft ruptures in a tertiary referral centre in the UK. We have examined the causes of traumatic corneal graft ruptures and the long-term visual outcome in patients with ruptured corneal grafts on prolonged follow-up.…”
Section: Introductionmentioning
confidence: 99%